Pertussis Reinfection in an Adult: A Cause of Persistent Cough Not to Be Ignored - Theocharis Koufakis; Anastasia Paschala; Dimitrios Siapardanis (Case Reports in Infectious Diseases)
Pertussis is traditionally considered as a disease of the childhood; however, accumulating evidence suggests a stable increase of its incidence among adults and adolescents, during the last decades. Despite the fact that reinfection after natural disease or vaccination is not uncommon, the index of clinical suspicion of pertussis diagnosis in adults remains low. In this article, we report a case of pertussis reinfection 30 years after natural infection, which was complicated by pneumonia, and we discuss our diagnostic and therapeutic approach, aiming to raise clinicians’ degree of suspicion regarding pertussis diagnosis in adults. Prompt recognition and appropriate therapy of adult patients can result in the effective control of the symptoms, prevention of severe complications, and spread of the infection to children; thus, they are of great clinical and public health importance.